A comparative study of carbon nanotube characteristics synthesized from various biomass precursors through hydrothermal techniques and their potential applications. Issue 1 (2nd January 2022) - J B, Mathangi; M, Helen Kalavathy
Abstract: Preparing low-cost carbon nanotubes (CNTs) from renewable biomass resources as cheap carbon precursors will potentially benefit industries and is given extraordinary importance. This article describes CNT synthesis from biomass precursors using the hydrothermal technique using ferrocene as a catalyst for energy storage and decontamination of the atmosphere. The prepared CNTs were characterized using XRD, Raman, and SEM analysis. Among the synthesized products, TGSD-CNT was further taken for application studies. TGSD-CNT with a band gap (2.01 eV) has become a hot spot in various scientific achievements such as mitigation of environmental pollution, generation of energy, and storage in the present study. The emission spectrum was studied using the 1931 chromaticity diagram of the Commission Internationale de I'eclairage (CIE) to investigate the TGSD-CNT dominant emission. Batch adsorption experiments were conducted for different operating parameters and a comparative analysis was performed to study the performance between CAC and the synthesized TGSD-CNT. Therefore, the conversion of available cheap biomass into high value-added materials such as CNT becomes practical, feasible and this reduces CNT's cost of production. The synthesized TGSD-CNT is therefore a useful material for applications such as sorption of heavy metal and photovoltaic devices.